1983
DOI: 10.1177/014107688307601012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Coronary Embolism: A Review1

Abstract: Coronary embolism is an uncommon but distinct clinical entity. It can be diagnosed clinically, and should be suspected when acute myocardial infarction occurs in association with an underlying condition which predisposes to embolism. The most common are valvular heart disease, a prosthetic heart valve, infective endocarditis, cardiomyopathy with mural thrombus and arrhythmia. The diagnosis may be obscured by atypical symptoms and transient ECG changes. The diagnosis is supported by the demonstration of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
0
31
0
4
Order By: Relevance
“…Platelet aggregation at poststenotic sites appears to be strictly dependent on the release of platelet agonists and, hence, is fundamentally different from the mechanism of microshear gradient-dependent platelet aggregation, earlier described by Nesbitt et al (16). Already in the 1970s, it was suggested that alterations in blood flow dynamics around atherosclerotic plaques link to occlusive thrombus formation (12), and that mild vascular damage in the presence of lumen reduction has thrombotic consequences, such as in the classical Foltz model of thromboembolism (18). Fluid dynamic studies from the 1990s reported that stenotic regions influenced platelet aggregation by way of flow perturbations and recirculation zones (19,20).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Platelet aggregation at poststenotic sites appears to be strictly dependent on the release of platelet agonists and, hence, is fundamentally different from the mechanism of microshear gradient-dependent platelet aggregation, earlier described by Nesbitt et al (16). Already in the 1970s, it was suggested that alterations in blood flow dynamics around atherosclerotic plaques link to occlusive thrombus formation (12), and that mild vascular damage in the presence of lumen reduction has thrombotic consequences, such as in the classical Foltz model of thromboembolism (18). Fluid dynamic studies from the 1990s reported that stenotic regions influenced platelet aggregation by way of flow perturbations and recirculation zones (19,20).…”
Section: Discussionmentioning
confidence: 88%
“…Intraluminal growth of a developing plaque, even in the absence of thrombus formation, will gradually alter the local blood flow dynamics (11). The flow disturbances at sites of severe stenosis may even lead to fatal occlusive thrombus formation in humans (12). Simulations indicate that plaque geometries induce gradients in pressure, flow velocity, and shear stress of the local blood flow, as a consequence of which autocrine agonists may get trapped that enhance platelet activation (13).…”
mentioning
confidence: 99%
“…Other causes of coronary embolism include atrial fibrillation, left atrial tumours, bacterial endocarditis, atrial and ventricular mural thrombus, syphilis and pulmonary vein thrombosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…As the incidence of mechanical valve surgery has increased, systemic thromboembolism became an important problem. Although coronary embolism due to mechanical valve thrombosis is encountered rarely, it is an important and serious complication (1). Here, we report a case of myocardial infarction caused by coronary embolism due to mechanical mitral valve thrombosis.…”
Section: Introductionmentioning
confidence: 92%
“…The incidence of systemic embolization with mechanical valves is 1% per year (1). Most cases present with cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%